New moving target Doppler centroid expression in geosynchronous SAR - Mounir Melzi (The Journal of Engineering, 2019)
Various techniques have been proposed in the literature to tackle the problem of moving target detection in the low-earth orbit synthetic aperture radar (LEO SAR) scenarios. Nevertheless, this issue has not been addressed yet in the geosynchronous synthetic aperture radar (GEO SAR) situation. This study points out the existing differences in the Doppler domain between GEO and LEO SAR imaging, and shows the advantages of using Doppler spectrum based-techniques to solve the multiple ground moving target indication issue in GEO SAR. Furthermore, it provides a new formulation for the moving target Doppler centroid in the GEO SAR case that consider the specific features of the GEO SAR imaging. Simulation results are provided to demonstrate the accuracy of the developed expression.